2012
DOI: 10.1007/s00192-012-1825-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of Macroplastique for treating female stress urinary incontinence

Abstract: Introduction and hypothesisMacroplastique® (polydimethylsiloxane injection) is a minimally invasive urethral bulking agent with global clinical literature describing its use over 20 years. This study critically assessed the safety and effectiveness outcomes for adult women treated with Macroplastique for stress urinary incontinence (SUI) through a systematic review and meta-analysis.MethodsA systematic review of the scientific literature from 1990 to 2010 was conducted in accordance with the Preferred Reportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 35 publications
0
49
1
2
Order By: Relevance
“…A meta‐analysis by Ghoniem and Miller reported a success rate of 64% at 18 months after MPQ in women with SUI 15 . Other long‐term findings have been reported by Tamanini et al 7 who used postoperative VLPP to establish a cure/improvement rate of 73% in 15 women followed for 60 months.…”
Section: Discussionmentioning
confidence: 84%
“…A meta‐analysis by Ghoniem and Miller reported a success rate of 64% at 18 months after MPQ in women with SUI 15 . Other long‐term findings have been reported by Tamanini et al 7 who used postoperative VLPP to establish a cure/improvement rate of 73% in 15 women followed for 60 months.…”
Section: Discussionmentioning
confidence: 84%
“…In fact, the moderate quality of these studies and the great heterogeneity did not allow a fair comparison between groups. In 2013, two reviews article on the efficacy of bulking agents were published [8,9]. Davis et al, in a descriptive review that included 45 articles on bulking agents for the treatment of SUI, concluded that in carefully selected patients, injectable biomaterials represent feasible alternatives to open surgical procedures as primary and secondary treatment options for SUI [8].…”
Section: Commentsmentioning
confidence: 97%
“…In the only currently available meta-analysis on the urethral bulking agents, Ghoniem and Miller considered only data focusing on one type of material (polydimethylsiloxane injection) and included a great proportion of non-randomized studies [9].…”
Section: Commentsmentioning
confidence: 99%
“…We found a rate of serious complications (Clavien-Dindo >2) of 18% in the GH group and 26% in the TRC, mainly due to the removal of (a part of) the implants under local or general anesthesia. In the meta-analysis of Ghoniem [23], no serious adverse events were recorded. In a systematic review performed by Kasi et al [24] in 2016, 8 studies were included with a total of 767 patients who were treated with Bulkamid ® .…”
Section: Discussionmentioning
confidence: 99%